Turbulance 2 : Fear Of Flying - Ching, Siu-Tung.; Ko, Eddy.; Jean Wang; Joey Wong; Shun Lau; Waise Lee; Yee Kwan Yan; Brigitte Lin (Lions Gate, 1992)
A royal official accompanies a Portuguese warship to the Black Cliffs to see the site of the defeat of the evil Invincible Asia, who attained supernatural abilities by following the sacred scroll and castrating himself. The official discovers that the Portuguese are actually after the sacred scroll, and then finds Invincible Asia him/herself, who is not actually dead. Invincible Asia seeks to destroy all the imposters or 'false Invincible Asias' who have assumed his/her place leading cults, whilst the Portuguese, a mysterious Japanese warlord and others search for Invincible Asia and the Sacred Scroll.
A royal official accompanies a Portuguese warship to the Black Cliffs to see the site of the defeat of the evil Invincible Asia...
Louis Cha
Language : English Subtitles : Chinese
Keywords: History; Romance; Action